(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
The study was carried out to assess the abundances, richness, diversity and status of tree species across five markets vicinities in Obi Local Government Area of Nasarawa State Nigeria. The five markets randomly selected included Daddere, Obi, Tudun Adabu, Agyragu and Adudu markets with all selected tree species identified at species level and the number of individuals enumerated. The result revealed the presence of 196 trees species belonging to 10 families in 19 deferent tree species. Daddare market recorded the highest diversity index of 1.798, while Obi, Adudu, Agyeragu and Tudun Adabu markets was 1.573, 1.407, 1.340, and 1.214 respectively. The Gamma diversity value was 2.209 for the tree species with the tree species richness for the Gamma tree species highest for Margaleaf value (3.40), Daddare market (1.780), Obi (1.763), Adudu (1.698) while, TudunAdabu recorded Margaleaf value (1.365) and Agyeragu recorded the least value (1.202). The status of tree species is relatively stable with only few tree species endangered and Azahdracta indica was the only trees species found across all the markets. Consequently, the tree species diversity and richness were relatively low which can be improved by shops owners in the markets by planting at least a tree in their shop environ.